Pengadaan Alat Produksi Guna Meningkatkan Produksi DUPITOS di Dusun Petung Sewu Kabupaten Malang - Eny Widiyowati; Bambang Suryanto; Ayu Sulasari; Masrevastuti Masrevastuti (Publisher UPT P2M Politeknik Negeri Malang, 2022)
Abstract Dusun Petungsewu is one of the hamlets producing quality corn gerit. The product diversification that has been carried out is in the form of tortilla chips, which are named Dupitos (Duwet Polinema Tortilla Chips). The production is carried out by the people of Dusun Petungsewu. The potential possessed by Dusun Petungsewu by processing Dupitos is quite large. This is because Dupitos products are healthy snacks that are suitable for consumption by all ages. Currently, Dupitos' production process still uses inadequate equipment. Therefore, this service aims to donate the equipment needed in the Dupitos production process so that the production process can run smoothly. The implementation of community service programs is carried out in the form of production equipment grants, knowledge transfer, questions and answers and evaluations. The results of the service show that the procurement of production equipment in the form of a dough rolling machine and dough thinning machine facilitates the Dupitos production process. Thus, partners can work more efficiently and effectively. This service provides several benefits both in terms of quality and quantity. It is hoped that the implementation of the service can provide benefits and help both partners to improve the quality and quantity of production. Keywords: Dupitos, Dusun Petungsewu, equipment assistance